Communication Without Borders: Integrating Sign Language in Restaurants for Maximum Inclusivity - Sanjaya, Ardi; Wulansari, Widi; Lailiyah, Nur (CV. Srikandi Kreatif Nusantara in collaboration with Institut Teknologi Mojosari Nganjuk, 2024)
Creating an inclusive and accessible environment in restaurants is essential, and integrating sign language as a medium of communication plays a pivotal role in achieving this goal. This article delves into the significance and effects of incorporating sign language into restaurant services to address the communication needs of deaf individuals. By adopting sign language, restaurants not only improve service quality but also broaden their clientele, including those who face challenges with verbal communication. Through a comprehensive literature review and analysis of case studies where restaurants have successfully implemented sign language, this study highlights the social, cultural, and economic advantages of such practices. It offers practical guidelines for staff training in sign language and the integration of supportive technologies. The goal is to illustrate how restaurants can transform into genuinely inclusive spaces, ensuring that all customers, regardless of their hearing abilities, can enjoy a pleasant and seamless dining experience. This approach not only fosters a more welcoming atmosphere but also enhances overall customer satisfaction and loyalty.